Risk assessments, quality protocols and other publically-available research reports supporting the risk estimates presented in "Environmental International Risk assessments for quality-assured, source-segregated composts and anaerobic digestates for a circular bioeconomy in the UK". - Pollard, Simon J. T.; Longhurst, Philip J.; Villa, Raffaella; Sakrabani, Ruben; Leinster, Paul; Tyrrel, Sean (Cranfield University, 2019)
Longhurst et al. (2019) Environment International. Risk assessments for quality-assured, source-segregated composts and anaerobic digestates for a circular bioeconomy in the UK. The publically-available risk assessments, quality protocols and other publically-available research reports supporting the risk estimates presented in this paper (accepted to ENVINT) are collated here. The Environment International paper reports residual risk estimates and hazard quotients for microbiological and chemical risks in quality-assured composts and digestates prepared under quality protocols from source-segregated biodegradable wastes. This CORD record here collates WRAP and associated research reports supporting the risk estimates and hazard quotients discussed in this summary paper, including risk assessments and quality protocols.
Keywords: risk assessment'; 'quality protocol'; 'compost'; 'digestate'; 'source segregated'; 'WRAP'; 'Environmental Engineering Modelling'; 'Environmental Technologies'; 'Fertilisers and Agrochemicals (Application etc.)'; 'Sustainable Agricultural Development'